A study on price elements in eleven terms in incoterms 2010 = Nghiên cứu về các yếu tố giá cả được sử dụng trong 11 điều kiện của “các điều khoản thương mại quốc tế 2010” - Nguyễn, Quỳnh Trang (2021)
The paper focused on investigating the price elements in 11 terms in Incoterms 2010 and these price terms‟ frequency of use in international transactions. The paper was conducted to find out the logistic costs included in eleven price terms given by seller in international transactions. Besides, the most favorable price terms used in seven main regions in the world and particularly in Vietnam were also pointed out along with giving reasons for their preference to businessmen. In order to achieve these aims, both quantitative and qualitative methods were employed. At the end of the paper, through data collection and analysis, the logistics costs included in each terms as well as the most dominant price terms in international transactions and Vietnam are pointed out clearly. Overall, the researcher has partially succeeded in providing readers with both useful knowledge about economic terminology and practical information about international business. However, there still exits some limitations which leave room for improvement of the study. Finally, the researcher also offers some suggestions for further studies in the future.